College Algebra (10th Edition)

Published by Pearson
ISBN 10: 0321979478
ISBN 13: 978-0-32197-947-6

Chapter 9 - Section 9.1 - Sequences - 9.1 Assess Your Understanding: 33

Answer

$a_n=(-1)^{n+1}(n)$

Work Step by Step

The terms, when the signs are ignored, are the whole numbers. This means that the formula for the $n^{th}$ term involves $n$. The sign of the terms alternate, starting with positive. This means that the formula for the $n^{th}$ term involves a power of $-1$. Since the first term is positive, the exponent/power of $-1$ is either $n+1$ or $n-1$. If $n+1$ is used, the formula for the $n^{th}$ term is: $a_n=(-1)^{n+1}(n)$ To check: n=1: $(-1)^{1+1}(1) = (-1)^2(1) = 1$ n=2: $(-1)^{2+1}(2) = (-1)^3(2) = -2$ n=3: $(-1)^{3+1}(3) = (-1)^4(3) = 3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.